Objective Measures to Characterize the Physiological Effects of Spinal Cord Stimulation in Neuropathic Pain: A Literature Review. Issue 2 (24th September 2018) - Sankarasubramanian, Vishwanath; Harte, Steven E.; Chiravuri, Srinivas; Harris, Richard E.; Brummett, Chad M.; Patil, Parag G.; Clauw, Daniel J.; Lempka, Scott F.
Abstract : Objective: The physiological mechanisms behind the therapeutic effects of spinal cord stimulation (SCS) are only partially understood. Our aim was to perform a literature review of studies that used objective measures to characterize mechanisms of action of SCS in neuropathic pain patients. Materials and Methods: We searched the PubMed data base to identify clinical studies that used objective measures to assess the effects of SCS in neuropathic pain. We extracted the study factors (e.g., type of measure, diagnoses, painful area[s], and SCS parameters) and outcomes from the included studies. Results: We included 67 studies. Of these, 24 studies used neurophysiological measures, 14 studies used functional neuroimaging techniques, three studies used a combination of neurophysiological and functional neuroimaging techniques, 14 studies used quantitative sensory testing, and 12 studies used proteomic, vascular, and/or pedometric measures. Our findings suggest that SCS largely inhibits somatosensory processing and/or spinal nociceptive activity. Our findings also suggest that SCS modulates activity across specific regions of the central nervous system that play a prominent role in the sensory and emotional functions of pain. Conclusions: SCS appears to modulate pain via spinal and/or supraspinal mechanisms of action (e.g., pain gating, descending pain inhibition). However, to better understand the mechanisms of action of SCS, we believe that it is necessary to carry out systematic, controlled, and well‐powered studies using objective patient measures. To optimize the clinical effectiveness of SCS for neuropathic pain, we also believe that it is necessary to develop and implement patient‐specific approaches.